Penilaian Sistem Transportasi yang Mengarah Pada Green Transportasi di Kota Surakarta - Andriani, Dian Maria; Yuliastuti, Nany (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Surakarta City Government has been designing its transportation system towards green transportation as a part of the eco city concept developed for the city in 2010. This study conducted evaluation on Surakarta City’s transportation system in its efforts to realize sustainable transportation in the city. This study employed quantitative approach through 3 analyses, comprising: (1) transportation system analysis regarding the system of activity, movement and network, (2) sustainable transportation analysis regarding transportation economic, social and environmental impacts, and (3) green transportation analysis regarding policy, mode choice and concept implementation. System evaluation analysis showed that the implementation of green transportation concept to realize sustainable transportation has been ‘quite successful’. Sustainable transportation analysis showed that the concept implementation has been ‘quite good’ and representative towards green transportation. However, the realization of green transportation is not to be recognized as ‘good’ due to many drawbacks in many aspects. This study found a need for an official document which explains, directs and regulates the implementation of green transportation concepts in Surakarta City.